The Differences in Imaging Findings Between Painless and Painful Osteoarthritis of the Hip. - Kijima, Hiroaki; Yamada, Shin; Konishi, Natsuo; Kubota, Hitoshi; Tazawa, Hiroshi; Tani, Takayuki; Suzuki, Norio; Kamo, Keiji; Okudera, Yoshihiko; Fujii, Masashi; Sasaki, Ken; Kawano, Tetsuya; et al. (Clinical Medicine Insights: Arthritis & Musculoskeletal Disorders, 2020)
Purpose: In osteoarthritis of the hip, the pain may be strong even if the deformity is mild, but the pain may be mild even if the deformity is severe. If the factors related to the pain can be identified on imaging, reducing such factors can alleviate the pain, and effective measures can be taken for cases where surgery cannot be performed. In addition, imaging findings related to the pain are also important information for determining the procedures and the timing of surgery. Thus, the purpose of this study was to identify the differences in features of osteoarthritis seen on imaging between painless and painful osteoarthritis of the hip. Methods: The subjects were the patients with hip osteoarthritis who visited our department in 2015 and who underwent x-ray, computed tomography (CT), and magnetic resonance imaging (MRI), a total of 29 patients (54 hip joints; mean age 63 years; 8 males and 21 females). The degree of osteoarthritis was determined using the Tönnis grade from the x-ray image. The cartilage morphology, intensity changes of bone marrow on MRI (subchondral bone marrow lesions [BMLs]), osteophytes, joint effusions, and paralabral cysts were scored based on the Hip Osteoarthritis MRI Scoring System (HOAMS). The cross-sectional area of the psoas major muscle at the level of the iliac crest was measured on CT, and the psoas index (PI; the cross-sectional area ratio of the psoas major muscle to the lumbar 4/5 intervertebral disc) was calculated to correct for the difference in physique. Then, the relationships between these and visual analog scale (VAS) scores of pains were evaluated. Results: The average VAS was 55.4 ± 39 mm. The PI and all items of HOAMS correlated with the VAS. The average VAS of Tönnis grade 3 osteoarthritis was 75.8 ± 26 mm. When investigating only Tönnis grade 3 osteoarthritis, the differences between cases with less than average pain and those with above average pain were the BML score in the central-inferior femoral head (P =.0213), the osteophyte score of the inferomedial femoral head (P =.0325), and the PI (P =.0292). Conclusion: Investigation of the differences between painless and painful osteoarthritis of the hip showed that the cases with more pain have BMLs of the femoral head on MRI that extend not only to the loading area, but also to the central-inferior area. Even with the same x-ray findings, the pain was stronger in patients with severe psoas atrophy. Thus, the instability due to muscle atrophy may also play a role in the pain of hip osteoarthritis.